War trauma and maternal–fetal attachment predicting maternal mental health, infant development, and dyadic interaction in Palestinian families. Issue 5 (3rd September 2017) - Punamäki, Raija-Leena; Isosävi, Sanna; Qouta, Samir R.; Kuittinen, Saija; Diab, Safwat Y.
ABSTRACT: Optimal maternal–fetal attachment (MFA) is believed to be beneficial for infant well-being and dyadic interaction, but research is scarce in general and among risk populations. Our study involved dyads living in war conditions and examined how traumatic war trauma associates with MFA and which factors mediate that association. It also modeled the role of MFA in predicting newborn health, infant development, mother–infant interaction, and maternal postpartum mental health. Palestinian women from the Gaza Strip ( N = 511) participated during their second trimester (T1), and when their infants were 4 (T2) and 12 (T3) months. Mothers reported MFA (interaction with, attributions to, and fantasies about the fetus), social support, and prenatal mental health (post-traumatic stress disorder, depression, and anxiety) at T1, newborn health at T2, and the postpartum mental health, infant's sensorimotor and language development, and mother–infant interaction (emotional availability) at T3. Results revealed, first, that war trauma was not directly associated with MFA but that it was mediated through a low level of social support and high level of maternal prenatal mental health problems. Second, intensive MFA predicted optimal mother-reported infant's sensorimotor and language development and mother–infant emotional availability but not newborn health or maternal postpartum mental health.